A survey on the use of blade tenderizers by beef fabrication plants - George-Evins, C.D.; Unruh, John A.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A questionnaire to determine the use of blade tenderizers in beef fabrication facilities was sent to 241 members of the North American Meat Processors Association (NAMP). Eighty-four percent of the 90 respondents used blade tenderizers. These subprimals were at least sometimes tenderized by the following percentages of respondents: tenderloins, 7.9; chuck cuts, 18; round cuts, 36; ribeyes, 38; strip loins, 56; and top sirloin butts, 62. If a processor blade-tenderized a particular cut, they tenderized a majority of their production for that cut, generally with multiple passes through the tenderizer. For example, the 62% of respondents who tenderized top sirloin butts tenderized 87% of their production of that cut with an average of 1.6 passes. Cuts were aged by 70.7% of respondents that used blade tenderizers. The average aging period was 20 days, and the range was 7 to 60 days. Our respondents fabricated 75.1% of their beef products for the hotel/restaurant industry, 13.3% for retail, and 6.0% for other markets such as export or warehouse distributors. Blade tenderization is used widely by NAMP members, most often on ribeyes, strip loins, and top sirloin butts, and often combined with aging.
Keywords: Beef; Blade tenderization